Successful and Less Successful Interventions: Stabilizing Iraq and Afghanistan1. Issue 4 (11th November 2013) - Romano, David; Calfano, Brian; Phelps, Robert
Abstract : The US troop surge and awakening movements are the two factors most often associated with the decrease of violence in Iraq after 2006. However, these policies, including a distinction between the Anbar Awakening and later Sons of Iraq (SOI) program, did not occur simultaneously. To date, it also has not been made clear whether the surge, Anbar Awakening, and/or SOI deserve credit as the intervention responsible for improving security conditions in Iraq. Hence, we compare the relative effects of these three interventions using Poisson autoregression models for interrupted time series to assess which policy reduced civilian and Coalition troop casualties in Iraq between 2004 and 2011. We find clear evidence that the non‐Anbar SOI rather than the troop surge reduced casualty rates in Iraq, though this effect distinction has not been made salient in policy circles, where the conventional wisdom of a combined effect for the surge and awakening councils persists. Given this, the same kind of "surge and local militia allies" strategy held significant appeal for NATO strategists in Afghanistan. Yet for reasons we consider in the second portion of this article, a number of more challenging factors bedeviled counterinsurgency there.